PERENCANAAN STRATEGI BERSAING SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN DI SEKOLAH SWASTA SALATIGA - Dewa Made Dwi Kamayuda; Mutia Ayu Krismanda (Satya Widya, 2016)
This study aimed to develop competitive strategy planning in increasing number of new students in one of the private schools in Salatiga. The Design of the study is research & development and in this study is limited to the product design stage alone that produce schools competitive strategy planning in increasing the number of new students. Research instruments for gathering data are observation, interviews, FGD and study documents. Data Analysis used SWOT analysis to analyze the internal and external factors such as the school’s strengths, weaknesses, opportunities and threats in determining the appropriate competitive strategies for schools. The result of SWOT analysis indicated that the school is in quadrant position SO (Strength Opportunity), which supports an aggressive strategy by using the power of the internal environment of the school to seize the opportunities from external environment. Competitive strategy planning of the school which suggested namely: (1) Education and training for teachers:- Develop active, innovative, creative, effective and fun learning through particpated in seminars, workshops or training from both inside and outside of the school; (2) Focus on internal and external customers: Optimizing program and extracurricular activities ranging from planning, implementation, and evaluation to achieve the targets that are expected to have an opportunity to join competition with other schools, develop character building programs for students, Conducting program fun day and parenting seminar on building relationships and smooth communication between schools and parents and provides knowledge about how to educating children; (3) Teamwork: Organize retreat educators to strengthen the relationship, teamwork and equalization of school vision, Build effective and organized alumni network; (4) Engage and empower employees: Forming the evaluation team and the subject leader as an effective and efficient way to monitor and ensure the ability of the teaching profession evolved in terms of competence.